Persepsi Guru terhadap Strategi Pembelajaran Membaca Bahasa Inggris di Sekolah Dasar - Nathasya Sardy; Ika Kana Trisnawati; Risa Fitria (Jurnal Elementaria Edukasia, 2023)
Given that reading is a key component of young students' learning of the English language, this study intends to examine teachers' perceptions on elementary students' English reading problems and the teaching strategies used in teaching English reading. The study collected data from six elementary school teachers who work in various Indonesian schools. Semi-structured interviews were employed in this study's qualitative research design, which was then analyzed thematically. The findings revealed that elementary students had a number of reading difficulties, including limited vocabulary, misspellings, and pronunciation errors. These difficulties were brought on by first language interference, demotivation, lack of focus, and lack of parental involvement. The interview results further revealed that teachers used game-based learning (GBL) to teach elementary-level English reading to provide a fun learning environment and a good first impression for the students. However, although GBL is strongly encouraged, the games utilized should be adapted for the age and academic ability of the young students. Thus, it is essential for teachers to develop lesson plans where the games need to be matched to the characteristics of the children while using GBL to teach English reading to increase the learning outcomes.